On classification with missing data using rough-neuro-fuzzy systems - Nowicki, Robert K. (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new approach to fuzzy classification in the case of missing data. Rough-fuzzy sets are incorporatedinto logical type neuro-fuzzy structures and a rough-neuro-fuzzy classifier is derived. Theorems which allow determiningthe structure of the rough-neuro-fuzzy classifier are given. Several experiments illustrating the performance of the roughneuro-fuzzy classifier working in the case of missing features are described.
Keywords: fuzzy sets; rough sets; neuro-fuzzy architectures; classification; missing data